2017
DOI: 10.1097/gox.0000000000001339
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Regrafting of the Split Thickness Skin Graft Donor Site Assists Healing

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The management of the donor site after splitthickness harvesting may be problematic due to delayed healing, especially in elderly patients, due to pain and discomfort at the donor site, or in patients with systemic comorbidities. 1,2 A wide variety of dressings are available but no widely approved material exists for these wounds. Various dressings raise issues regarding low absorption to exudate, desiccation, frequent dressing changes, developing resistance to microbes, or price.…”
Section: Introductionmentioning
confidence: 99%
“…The management of the donor site after splitthickness harvesting may be problematic due to delayed healing, especially in elderly patients, due to pain and discomfort at the donor site, or in patients with systemic comorbidities. 1,2 A wide variety of dressings are available but no widely approved material exists for these wounds. Various dressings raise issues regarding low absorption to exudate, desiccation, frequent dressing changes, developing resistance to microbes, or price.…”
Section: Introductionmentioning
confidence: 99%
“…4 Bradow et al stated that it would be difficult to argue against the value of routinely regrafting in the patients expected to have poor reepithelialization potential but that not all patients may benefit of regrafting because of the aesthetically displeasing result that is typical for a meshed skin graft. 1 Our case shows that in healthy, young individuals the additional value of regrafting is indeed not so clear, since the appearance and patients' opinion of the regrafted site changed over time. Our case is a clear example of how the regrafted part can eventually develop into an aesthetically worse result with the displeasing aspects of a meshed skin graft (e.g., mixed pigmentation, irregular surface) after initial encouraging results, even though the non-grafted part took longer to heal.…”
Section: Discussionmentioning
confidence: 72%
“…After Thompson et al described better scar quality of donor sites after regrafting, several other studies reported quicker reepithelialization, reduced pain scores, and a good cosmetic appearance without an increase in complications. [1][2][3][4][5] However, studies with long-term results on donor site outcome are lacking. Bian et al were the only investigators who used a validated scale (the Vancouver Scar Scale) and a control group to assess scar quality and reported a beneficial outcome of regrafting compared with occlusive hydrocellular dressings and paraffin gauze at 1 year follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations